Hormone and implant osseointegration: Elaboration of the relationship among function, preclinical, and clinical practice - Yi, Ming; Yin, Ying; Sun, Jiwei; Wang, Zeying; Tang, Qingming; Yang, Cheng (Frontiers in Molecular Biosciences, 2022)
As clusters of peptides or steroids capable of high-efficiency information transmission, hormones have been substantiated to coordinate metabolism, growth and development and other physiological processes, especially bone physiology and repair metabolism. In recent years, the application of hormones for implant osseointegration has become a research hotspot. Herein, we provide a comprehensive overview of the relevant reports on endogenous hormones and corresponding supplementary preparations to explore the association between hormones and the prognosis of implants. We also discuss the effects and mechanisms of insulin, PTH, melatonin, vitamin D and growth hormone on osseointegration at the molecular and body levels to provide the foothold and guide future research on the systemic conditions that affect the implantation process and expand the relative contraindications of the implant, and the pre-and post-operative precautions. This review shows that systemic hormones can regulate the osseointegration of oral implants through endogenous or drug delivery methods.